Silicon Confers Soybean Resistance to Salinity Stress Through Regulation of Reactive Oxygen and Reactive Nitrogen Species - Chung, Yong Suk; Kim, Ki-Seung; Hamayun, Muhammad; Kim, Yoonha (Frontiers in Plant Science, 2020)
Salt stress is one of the major abiotic stressors that causes huge losses to the agricultural industry worldwide. Different strategies have been adopted over time to mitigate the negative impact of salt stress on plants and reclaim salt-affected lands. In the current study, we used silicon (Si) as a tool for salinity alleviation in soybean and investigated the influence of exogenous Si application on the regulation of reactive oxygen and reactive nitrogen species and other salt stress–related parameters of the treated plants. Our results revealed that the canopy temperature was much higher in sole NaCl–treated plants but declined in Si + NaCl–treated plants. Furthermore, the chlorophyll contents decreased with sole NaCl treatment, whereas Si + NaCl–treated plants showed improved chlorophyll contents. In addition, Si application normalized the photosynthetic responses, such as transpiration rate (E) and net photosynthesis rate (PN) in salt-treated plants, and reduced the activity of ascorbate peroxidase and glutathione under salt stress. The expression levels of antioxidant-related genes GmCAT1, GmCAT2, and GmAPX1 started to decline at 12 h after addition of Si to NaCl-treated plants. Similarly, the S-nitrosothiol and nitric oxide (NO)–related genes were upregulated in the salt stress condition but reduced after Si supplementation. Si application downregulated genes associated with reactive oxygen species and reactive nitrogen species and reduced enzymatic and non-enzymatic antioxidants of the treated plants. Results of the current study conclude that Si mitigated the adverse effects of NaCl-induced stress by modulating the crosstalk between antioxidants and NO scavengers. It is suggested that Si may be used in agricultural systems for alleviating salt stress.